Conductive member for electrophotographic device
By forming a surface layer of convex portions of a specific shape and size on the surface of the conductive member, the problem of difficulty in removing buried dirt and uneven surface concave and convexity in the prior art is solved, and the effect of effectively suppressing dirt adhesion and improving the surface cleanliness of the conductive member is achieved.
Patent Information
- Application Number
- CN202380059762.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-27
- Filing Date
- 2023-08-07
- Publication Date
- 2025-04-25
AI Technical Summary
The prior art is difficult to effectively remove buried dirt on the surface of the conductive member, and the aggregation of the particles for roughness formation leads to uneven surface convexity, which easily leads to dirt accumulation.
An elastomeric layer with a plurality of convex portions is used, the front end of the convex portion is composed of a curved surface, the height is 1.0 nm or more and 10 nm or less, the width is 1.0 nm or more and 100 nm or less, and the ratio of width to interval is 0.5 or more and 1.5 or less. The surface layer is composed of a styrene-butadiene block copolymer, contains carbon black, and forms fine and uniform convex portions through self-organization of the diblock copolymer.
Effectively suppress the adhesion of toner and paper dust, ensure the surface of the conductive member is clean, improve image quality, and have excellent electrical conductivity.
Smart Images

Figure CN119895336A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a conductive member for electrophotographic equipment such as a charging roller and a developing roller which is preferably used in electrophotographic equipment such as a copying machine, a printer, and a facsimile machine which adopt an electrophotographic method. Background Art
[0002] In an electrophotographic device such as a copier, printer, or fax machine that uses an electrophotographic method, a photosensitive drum is usually installed, and roller-shaped conductive members such as a charging roller, a developing roller, a transfer roller, and a toner supply roller, a cleaning member such as a cleaning blade, and belt-shaped conductive members such as a transfer belt and a fixing belt are arranged around the photosensitive drum. Copying and printing based on such an electrophotographic device are performed by forming an original image into an electrostatic latent image on the photosensitive drum, causing toner to adhere to the electrostatic latent image to form a toner image, and transferring the toner image to copy paper.
[0003] If toner, toner external additives, paper dust, and other dirt adhere to the surface of the conductive member, it will cause poor image. For example, if the charging roller is contaminated by toner, paper dust, etc. that fall on the photosensitive drum, the charging performance will be reduced, and the photosensitive drum cannot be charged evenly, resulting in poor image. In recent years, if a cleaning blade is not provided due to low power consumption of equipment, the demand for stain resistance has further increased.
[0004] As a countermeasure against such contamination, there are methods of adding a modifier to a surface material to improve the water repellency and oil repellency of the surface, and methods of adding roughness forming particles to the surface material to form surface irregularities.
[0005] Patent Document 1 proposes a charging roller having a nanostructure layer having a plurality of columnar protrusions on its surface as a surface layer in order to suppress adhesion of foreign matter such as toner, toner external additives, and abrasion powder of a photosensitive drum.
[0006] Furthermore, Patent Document 2 proposes a charging roller having a nano-patterned layer with a plurality of groove-shaped concave-convex portions parallel to each other as a surface layer in order to suppress the adhesion of agglomerates (foreign matter) generated during use. The groove-shaped concave-convex portions are formed by etching a microphase separation structure of a layered structure using the difference in carbon density of monomer units.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Application Publication No. 2013-076862
[0010] Patent Document 2: Japanese Patent Application Publication No. 2013-076861 Summary of the invention
[0011] Problems to be solved by the invention
[0012] As a way of attaching dirt such as colorant, colorant external additives, paper dust, etc. to the surface of the conductive member, in addition to surface dirt in which the dirt only adheres to the surface of the conductive member, physical dirt in which the dirt is embedded or drilled into the surface of the conductive member has also been confirmed. In the method of adding a modifier to the surface material, surface dirt can be removed, but it is difficult to fully remove physical dirt embedded in the surface. In addition, the method of adding roughness forming particles to the surface material is difficult to form uniform surface unevenness due to the aggregation of particles. In addition, the roughness forming particles are too large relative to the dirt, so the dirt easily accumulates between the protrusions.
[0013] The surface layer of the charging roller of Patent Document 1 is a nanostructure layer having a plurality of convex portions of a columnar structure, and the surface in contact with dirt such as toner is a flat surface at the front end of the convex portion of the columnar structure. Thus, in the surface layer of the charging roller of Patent Document 1, the contact area with dirt becomes larger, so dirt is easily attached.
[0014] The surface layer of the charging roller of Patent Document 2 is a nano-pattern layer having a plurality of groove-shaped concave and convex shapes formed by etching the microphase separation structure of the layered structure, forming a concave and convex shape of the layered structure. On the surface of the charging roller of Patent Document 2, the concave and convex shape is formed by convex stripes and concave stripes, and the surface in contact with dirt such as toner is the convex stripes, so the contact area with the dirt is large and the dirt is easily attached. In particular, the attachment of dirt such as external additives of small-sized toners and paper dust is more significant than that of large-sized toners.
[0015] An object of the present invention is to provide a conductive member for an electrophotographic device that suppresses adhesion of toner and paper dust.
[0016] Means used to solve problems
[0017] The conductive component for the electronic photographic device involved in the present invention comprises an elastomer layer and a surface layer formed on the outer peripheral surface of the elastomer layer, a plurality of protrusions are formed on the outer peripheral surface of the surface layer, the front ends of the protrusions are composed of curved surfaces, the height of the protrusions is greater than 1.0 nm and less than 10 nm, the width of the protrusions is greater than 1.0 nm and less than 100 nm, and the width of the protrusions is greater than 0.5 and less than 1.5 relative to the size of the interval between the protrusions.
[0018] The convex portion is preferably hemispherical. The surface roughness Ra of the surface layer is preferably 0.5 nm or more and 10 nm or less. The interval between the convex portions is preferably 1.0 nm or more and 100 nm or less. The surface layer is preferably composed of styrene-butadiene block copolymer. The styrene amount of the styrene-butadiene block copolymer is preferably 71% by mass or more and 85% by mass or less, and the styrene block copolymer amount of the styrene-butadiene block copolymer is preferably 40 mol% or more and 75 mol% or less. The surface layer preferably contains carbon black. The surface layer is preferably composed of a self-organized film of a diblock copolymer. The diblock copolymer is preferably composed of a phase composed of a block polymer component on one side and a phase composed of a block polymer component on the other side arranged in a thickness direction. The diblock copolymer is preferably a styrene-butadiene block copolymer, and a phase composed of a styrene block polymer component is arranged on a phase composed of a butadiene block polymer component. The convex portion is preferably composed of a phase composed of a styrene block polymer component in the diblock copolymer.
[0019] (1) The conductive component for an electronic photographic device involved in the present invention comprises an elastomer layer and a surface layer formed on the outer peripheral surface of the elastomer layer, wherein a plurality of protrusions are formed on the outer peripheral surface of the surface layer, wherein the front ends of the protrusions are composed of curved surfaces, the height of the protrusions is greater than 1.0 nm and less than 10 nm, the width of the protrusions is greater than 1.0 nm and less than 100 nm, and the width of the protrusions is greater than 0.5 and less than 1.5 relative to the size of the interval between the protrusions.
[0020] (2) In the above (1), the convex portion is preferably hemispherical.
[0021] (3) In the above (1) or (2), the surface roughness Ra of the surface layer is preferably not less than 0.5 nm and not more than 10 nm.
[0022] (4) In any one of the above (1) to (3), the interval between the protrusions is preferably not less than 1.0 nm and not more than 100 nm.
[0023] (5) In any one of the above (1) to (4), the surface layer is preferably composed of a styrene-butadiene block copolymer.
[0024] (6) In addition to the above (5), the styrene content of the styrene-butadiene block copolymer is preferably 71% by mass or more and 85% by mass or less, and the styrene block copolymer content of the styrene-butadiene block copolymer is preferably 40 mol% or more and 75 mol% or less.
[0025] (7) In any one of the above (1) to (6), the surface layer preferably contains carbon black.
[0026] (8) In any one of the above (1) to (7), the surface layer is preferably composed of a self-assembled film of a diblock copolymer.
[0027] (9) In addition to the above (8), the diblock copolymer preferably has a structure in which a phase composed of one block polymer component and a phase composed of the other block polymer component are arranged in parallel in the thickness direction.
[0028] (10) In the above (9), the diblock copolymer is preferably a styrene-butadiene block copolymer, wherein a phase consisting of a styrene block polymer component is disposed on a phase consisting of a butadiene block polymer component.
[0029] (11) In the above (10), the convex portion is preferably constituted by a phase consisting of a styrene block polymer component in the diblock copolymer.
[0030] Effects of the Invention
[0031] According to the conductive component for electronic photographic equipment involved in the present invention, a plurality of protrusions are formed on the outer peripheral surface of the surface layer, the front end of the protrusion is composed of a curved surface, the height of the protrusion is greater than 1.0nm and less than 10nm, the width of the protrusion is greater than 1.0nm and less than 100nm, and the width of the protrusion is greater than 0.5 and less than 1.5 relative to the size of the spacing between the protrusions, thereby suppressing the adhesion of colorant and paper dust.
[0032] Furthermore, if the convex portion is hemispherical, the tip of the convex portion is a curved surface, and the contact area with dirt such as toner and paper dust is small, thereby achieving an excellent effect of suppressing the adhesion of dirt such as toner and paper dust.
[0033] Furthermore, when the surface roughness Ra of the surface layer is 0.5 nm or more and 10 nm or less, it is an appropriate roughness for dirt such as toner and paper dust, and thus the effect of suppressing the adhesion of dirt such as toner and paper dust is excellent.
[0034] Furthermore, when the interval between the convex portions is 1.0 nm or more and 100 nm or less, a plurality of convex portions are evenly arranged on the outer peripheral surface of the surface layer, and thus the effect of suppressing the adhesion of dirt such as toner and paper dust is excellent.
[0035] Furthermore, if the surface layer is composed of a styrene-butadiene block copolymer, a plurality of convex portions can be finely and uniformly formed on the outer peripheral surface of the surface layer by self-organization of the block copolymer, thereby achieving an excellent effect of suppressing the adhesion of dirt such as toner and paper dust.
[0036] Moreover, if the amount of styrene in the styrene-butadiene block copolymer is 71% by mass or more and 85% by mass or less, and the amount of styrene block copolymer in the styrene-butadiene block copolymer is 40 mol% or more and 75 mol% or less, it is easy to form a convex portion of appropriate size. In addition, it is not easy to form a layered structure (a fine pattern such as wrinkles). Thus, it is excellent in removing relatively large dirt such as toner. In addition, it is excellent in suppressing the contact area with relatively small dirt such as paper dust and toner external additives, suppressing the adhesion of small dirt and removing the small dirt.
[0037] Furthermore, when the surface layer contains carbon black, excellent electrical conductivity can be exhibited.
[0038] Furthermore, if the surface layer is composed of a self-assembled film of a diblock copolymer, a plurality of convex portions can be finely and uniformly formed on the outer peripheral surface of the surface layer, thereby achieving an excellent effect of suppressing the adhesion of dirt such as toner and paper dust.
[0039] Furthermore, if the diblock copolymer is composed of a phase composed of one block polymer component and a phase composed of another block polymer component arranged in the thickness direction, a plurality of convex portions can be finely and uniformly formed on the outer peripheral surface of the surface layer by self-organization of the block copolymer, thereby achieving an excellent effect of suppressing the adhesion of dirt such as toner and paper dust.
[0040] Furthermore, if the diblock copolymer is a styrene-butadiene block copolymer, and a phase composed of a styrene block polymer component is disposed on a phase composed of a butadiene block polymer component, a plurality of convex portions can be finely and uniformly formed on the outer peripheral surface of the surface layer by self-organization of the block copolymer, thereby achieving an excellent effect of suppressing the adhesion of dirt such as toner and paper dust.
[0041] Furthermore, if the convex portions are composed of a phase composed of the styrene block polymer component in the diblock copolymer, a plurality of convex portions can be finely and uniformly formed on the outer peripheral surface of the surface layer by self-organization of the block copolymer, thereby achieving an excellent effect of suppressing the adhesion of dirt such as toner and paper dust. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 (a) is a schematic diagram of the appearance of a conductive roller for an electrophotographic device according to one embodiment of the present invention, Figure 1 (b) in the figure is its radial cross-sectional view.
[0043] Figure 2 It is an enlarged schematic diagram of the cross section of the surface layer.
[0044] Figure 3 This is a schematic diagram illustrating the self-organization of the surface material.
[0045] Figure 4 (a) is a schematic diagram of the appearance of a conductive belt for an electrophotographic device according to one embodiment of the present invention, Figure 4 (b) in the figure is its radial cross-sectional view.
[0046] Figure 5 These are magnified photographs (1 μm×1 μm) of the surface layers of Examples and Comparative Examples. DETAILED DESCRIPTION
[0047] The conductive member for an electrophotographic device according to the present invention (hereinafter, sometimes referred to as the conductive member) is described in detail. The conductive member comprises an elastomer layer and a surface layer formed on the outer peripheral surface of the elastomer layer. The conductive member is preferably used as a conductive roller such as a charging roller, a developing roller, a transfer roller, a toner supply roller, an intermediate transfer belt, a paper transfer conveyor belt, an endless belt (conductive belt) such as a fixing belt, etc. used in an electrophotographic device such as a copier, a printer, a fax machine, etc. that adopts an electrophotographic method.
[0048] Figure 1 A conductive roller according to one embodiment of the present invention is shown. Figure 2 An enlarged schematic view showing a cross section of a surface layer of the conductive roller. Figure 3 A schematic diagram illustrating the self-organization of the surface material is shown. Figure 4 A conductive tape according to one embodiment of the present invention is shown.
[0049] The conductive roller 10 includes a shaft 12, an elastic layer 14 formed on the outer peripheral surface of the shaft 12, and a surface layer 16 formed on the outer peripheral surface of the elastic layer 14. The elastic layer 14 is a layer (base layer) that serves as a base of the conductive roller 10. The surface layer 16 is formed as a layer exposed on the surface of the conductive roller 10.
[0050] The shaft body 12 is not particularly limited as long as it has conductivity. Specifically, it can be a solid body made of metal such as iron, stainless steel, aluminum, or a core rod composed of a hollow body. An adhesive, a primer, etc. may be applied to the surface of the shaft body 12 as needed. The adhesive, the primer, etc. may also be made conductive as needed.
[0051] The elastic layer 14 contains a cross-linked rubber. The elastic layer 14 is formed of a conductive rubber composition containing an uncross-linked rubber. The cross-linked rubber is obtained by cross-linking an uncross-linked rubber. The uncross-linked rubber may be a polar rubber or a non-polar rubber.
[0052] Polar rubber is a rubber having a polar group, and examples of the polar group include chloro group, nitrile group, carboxyl group, epoxy group, etc. As polar rubber, specifically, examples include epichlorohydrin rubber, nitrile rubber (NBR), polyurethane rubber (U), acrylic rubber (copolymer of acrylate and 2-chloroethyl vinyl ether, ACM), chloroprene rubber (CR), epoxidized natural rubber (ENR), etc. Among polar rubbers, epichlorohydrin rubber and nitrile rubber (NBR) are more preferred from the viewpoint that the volume resistivity is particularly easy to be reduced.
[0053] Examples of the epichlorohydrin rubber include homopolymers of epichlorohydrin (CO), epichlorohydrin-ethylene oxide copolymers (ECO), epichlorohydrin-allyl glycidyl ether copolymers (GCO), and epichlorohydrin-ethylene oxide-allyl glycidyl ether terpolymers (GECO).
[0054] As the polyurethane rubber, there can be cited polyether-type polyurethane rubber having an ether bond in the molecule. The polyether-type polyurethane rubber can be produced by reacting a polyether having a hydroxyl group at both ends with a diisocyanate. The polyether is not particularly limited, and polyethylene glycol, polypropylene glycol, etc. can be cited. The diisocyanate is not particularly limited, and toluene diisocyanate, diphenylmethane diisocyanate, etc. can be cited.
[0055] Examples of the non-polar rubber include silicone rubber (Q), isoprene rubber (IR), natural rubber (NR), styrene-butadiene rubber (SBR), butadiene rubber (BR), etc. Among the non-polar rubbers, silicone rubber is more preferred from the viewpoints of low hardness and resistance to aging (excellent elastic recovery).
[0056] The elastic layer 14 preferably includes at least one of isoprene rubber, nitrile rubber, and epichlorohydrin rubber. If the elastic layer 14 includes at least one of isoprene rubber, nitrile rubber, and epichlorohydrin rubber, the compression permanent deformation is small, and the generation of a stripe image corresponding to the deformed portion when the conductive layer 10 is installed is suppressed.
[0057] Examples of the crosslinking agent include sulfur crosslinking agents, peroxide crosslinking agents, and dechlorination crosslinking agents. These crosslinking agents may be used alone or in combination of two or more.
[0058] Examples of the sulfur crosslinking agent include conventionally known sulfur crosslinking agents such as powdered sulfur, precipitated sulfur, colloidal sulfur, surface-treated sulfur, insoluble sulfur, sulfur chloride, thiuram-based vulcanization accelerators, and polymer polysulfides.
[0059] Examples of the peroxide crosslinking agent include conventionally known peroxide crosslinking agents such as peroxyketal, dialkyl peroxide, peroxyester, ketone peroxide, peroxydicarbonate, diacyl peroxide, and hydroperoxide.
[0060] Examples of the dechlorination crosslinking agent include dithiocarbonate compounds, more specifically, quinoxaline-2,3-dithiocarbonate, 6-methylquinoxaline-2,3-dithiocarbonate, 6-isopropylquinoxaline-2,3-dithiocarbonate, and 5,8-dimethylquinoxaline-2,3-dithiocarbonate.
[0061] The amount of the crosslinking agent is preferably in the range of 0.1 to 2 parts by mass, more preferably 0.3 to 1.8 parts by mass, and even more preferably 0.5 to 1.5 parts by mass, based on 100 parts by mass of the uncrosslinked rubber, from the viewpoint of preventing bleeding.
[0062] When a dechlorination crosslinking agent is used as a crosslinking agent, a dechlorination crosslinking accelerator can be used in combination. As a dechlorination crosslinking accelerator, 1,8-diazabicyclo-(5,4,0)-undec-7-ene (hereinafter referred to as DBU) or its weak acid salt can be listed. The dechlorination crosslinking accelerator can be used in the form of DBU, but from the perspective of its handling, it is preferably used in the form of its weak acid salt. As weak acid salts of DBU, carbonates, stearates, 2-ethylhexanoates, benzoates, salicylates, 3-hydroxy-2-naphthoates, phenolic resin salts, 2-mercaptobenzothiazole salts, 2-mercaptobenzimidazole salts, etc. can be listed.
[0063] The content of the dechlorination crosslinking accelerator is preferably in the range of 0.1 to 2 parts by mass, more preferably 0.3 to 1.8 parts by mass, and even more preferably 0.5 to 1.5 parts by mass, based on 100 parts by mass of the uncrosslinked rubber, from the viewpoint of preventing bleeding.
[0064] In order to impart conductivity, a conductive agent may be added to the elastomer layer 14. Examples of the conductive agent include electronic conductive agents and ionic conductive agents. Examples of electronic conductive agents include carbon black, graphite, and conductive metal oxides. Examples of conductive metal oxides include conductive titanium oxides, conductive zinc oxides, and conductive tin oxides. Examples of ionic conductive agents include quaternary ammonium salts, borates, and surfactants. In addition, various additives may be appropriately added to the elastomer layer 14 as needed. Examples of additives include lubricants, vulcanization accelerators, antioxidants, light stabilizers, viscosity modifiers, processing aids, flame retardants, plasticizers, foaming agents, fillers, dispersants, defoaming agents, pigments, and mold release agents.
[0065] The volume resistivity of the elastic layer 14 can be adjusted to a predetermined value by the type of crosslinked rubber, the amount of ion conductive agent, the amount of electronic conductive agent, etc. The volume resistivity of the elastic layer 14 is appropriately set to 10 2 ~10 10Ω·cm, 10 3 ~10 9 Ω·cm, 10 4 ~10 8 The range of Ω·cm or the like may be sufficient.
[0066] The thickness of the elastic layer 14 is not particularly limited, and may be appropriately set within a range of 0.1 to 10 mm, etc., depending on the intended use.
[0067] The surface layer 16 functions as a protective layer of the roller surface. A plurality of convex portions 18 are formed on the outer peripheral surface of the surface layer 16. The convex portion 18 is hemispherical, and the front end of the convex portion 18 is formed by a curved surface. The height h of the convex portion 18, the width W of the convex portion 18, and the width W of the convex portion 18 relative to the interval d of the convex portion 18 are within a specific range. In this way, the surface layer 16 has a plurality of fine and uniform convex portions 18 on its outer peripheral surface, so that dirt such as toner, toner external additives, and paper dust slides off, and the adhesion of dirt (toner and paper dust) is suppressed.
[0068] The height h of the convex portion 18 is greater than 1.0 nm and less than 10 nm. If the height h of the convex portion 18 is less than 1.0 nm, the convex portion 18 is too small, and the effect of removing relatively large dirt (about 5 μm) such as colorant is reduced. On the other hand, if the height h of the convex portion 18 is greater than 10 nm, the convex portion 18 is too large, and the contact area with relatively small dirt (about 100 nm) such as paper dust and colorant external additives becomes too large, and small dirt is easy to adhere and the effect of removing the small dirt is reduced. Moreover, from the above viewpoint, the height h of the convex portion 18 is preferably greater than 1.5 nm, more preferably greater than 2.0 nm, and further preferably greater than 2.5 nm. In addition, the height h of the convex portion 18 is preferably less than 9.0 nm, more preferably less than 8.0 nm, and further preferably less than 7.0 nm.
[0069] In the hemispherical convex portion 18, the width W of the convex portion 18 represents the diameter (outer diameter). The width W of the convex portion 18 is greater than 1.0nm and less than 100nm. If the width W of the convex portion 18 is less than 1.0nm, the convex portion 18 is too small, and the effect of removing relatively large dirt such as colorant is reduced. On the other hand, if the width W of the convex portion 18 is greater than 100nm, the convex portion 18 is too large, and the contact area with relatively small dirt such as paper dust and toner external additives becomes too large, small dirt is easy to adhere and the effect of removing the small dirt is reduced. Moreover, from the above viewpoint, the width W of the convex portion 18 is preferably greater than 5.0nm, more preferably greater than 10nm, further preferably greater than 20nm, and particularly preferably greater than 40nm. In addition, the width W of the convex portion 18 is preferably less than 90nm, more preferably less than 80nm, and further preferably less than 70nm.
[0070] The interval d between the protrusions 18 is preferably greater than 1.0nm and less than 100nm. If the interval d between the protrusions 18 is less than 1.0nm, the protrusions 18 are easily connected to form convex strips, and the contact area with relatively small dirt such as paper dust and colorant external additives becomes too large, small dirt is easy to adhere and the effect of removing the small dirt is reduced. On the other hand, if the interval d between the protrusions 18 is greater than 100nm, the interval d between the protrusions 18 is too large, the number of protrusions 18 is small, and the effect of dirt falling is reduced. Moreover, from the above viewpoint, the interval d between the protrusions 18 is preferably greater than 5.0nm, more preferably greater than 10nm, further preferably greater than 20nm, and particularly preferably greater than 40nm. In addition, the interval d between the protrusions 18 is preferably less than 90nm, more preferably less than 80nm, and further preferably less than 70nm.
[0071] Moreover, the width W of the convex portion 18 is preferably greater than 0.5 and less than 1.5 relative to the size of the interval d between the convex portions 18. If the width W of the convex portion 18 is less than 0.5 relative to the size of the interval d between the convex portions 18, the interval d between the convex portions 18 is too large, the number of the convex portions 18 decreases, and the effect of dropping the dirt is reduced. On the other hand, if the width W of the convex portion 18 is greater than 1.5 relative to the size of the interval d between the convex portions 18, the convex portions 18 are easily connected to form convex strips, and the contact area with relatively small dirt such as paper dust and toner external additives becomes too large, small dirt is easy to adhere and the effect of removing the small dirt is reduced. Moreover, from the above viewpoint, the width W of the convex portion 18 is preferably greater than 0.6 relative to the size of the interval d between the convex portions 18, more preferably greater than 0.7, and further preferably greater than 0.8. In addition, the width W of the convex portion 18 is preferably less than 1.4 relative to the size of the interval d between the convex portions 18, more preferably less than 1.3, and further preferably less than 1.2.
[0072] The surface roughness Ra of the surface layer 16 is preferably 0.5 nm or more and 10 nm or less. If the surface roughness Ra is less than 0.5 nm, the surface roughness is too small, and the effect of removing relatively large dirt such as toner is reduced. On the other hand, if the surface roughness Ra is greater than 10 nm, the surface roughness is too large, and the contact area with relatively small dirt such as paper dust and toner external additives becomes too large, small dirt is easy to adhere and the effect of removing the small dirt is reduced. If the surface roughness Ra is 0.5 nm or more and 10 nm or less, it is an appropriate roughness for dirt such as toner and paper dust, so the effect of suppressing the adhesion of dirt such as toner and paper dust is excellent. In addition, from the above viewpoint, the surface roughness Ra is preferably 0.8 nm or more, and more preferably 2.0 nm or more. In addition, the surface roughness Ra is preferably 5.0 nm or less, more preferably 4.0 nm or less, and further preferably 3.0 nm or less.
[0073] The height h of the convex portion 18, the width W of the convex portion 18, the interval d of the convex portion 18, and the surface roughness Ra can be obtained by image analysis using a height image of a scanning probe microscope (SPM). The interval d of the convex portion 18 can be obtained based on the lengths of the highest points of adjacent convex portions 18. The surface roughness Ra is the arithmetic mean roughness. After obtaining the SPM height image from any two points of the surface layer 16, each value is calculated for any three points in one place, and each value is expressed by its average.
[0074] The fine and uniform concavo-convex structure of the surface layer 16 can be formed by various methods, for example, it can be formed by the self-organization of a diblock copolymer. Thus, it is possible to effectively form a plurality of optimal convex portions 18, which are formed into a fine and uniform concavo-convex structure. The diblock copolymer is preferably a combination of a soft polymer and a rigid polymer. As a soft polymer, butadiene, isoprene, polyethylene oxide, polyacrylic acid, etc. can be listed. As a rigid polymer, styrene, polymethyl methacrylate, etc. can be listed. As a diblock copolymer, styrene-butadiene block copolymer, styrene-isoprene diblock copolymer, etc. can be listed. Among them, styrene-butadiene block copolymer is particularly preferred.
[0075] The amount of styrene in the styrene-butadiene block copolymer is preferably 71% by mass or more and 85% by mass or less, and the amount of styrene block copolymer in the styrene-butadiene block copolymer is preferably 40 mol% or more and 75 mol% or less. If the amount of styrene is 71% by mass or more and the amount of styrene block copolymer is 40 mol% or more, it is easy to form a convex portion 18 of an appropriate size that is not too small. Thus, it is excellent to remove relatively large dirt such as toner. In addition, if the amount of styrene is 85% by mass or less and the amount of styrene block copolymer is 75 mol% or less, it is easy to form a convex portion 18 of an appropriate size that is not too large. In addition, it is not easy to form a layered structure (a fine pattern such as wrinkles). Thus, the contact area with relatively small dirt such as paper dust and toner external additives is suppressed, and the adhesion of small dirt is suppressed and the effect of removing the small dirt is excellent. In addition, from the above viewpoint, it is more preferred that the above styrene amount is 73% by mass or more and the above styrene block copolymer amount is 45 mol% or more, and it is further preferred that the above styrene amount is 75% by mass or more and the above styrene block copolymer amount is 50 mol% or more. In addition, from the above viewpoint, it is more preferred that the above styrene amount is 80% by mass or less and the above styrene block copolymer amount is 70 mol% or less, and it is further preferred that the above styrene amount is 78% by mass or less and the above styrene block copolymer amount is 65 mol% or less. The styrene amount can be calculated by NMR.
[0076] The molecular weight of the styrene-butadiene block copolymer is preferably Mw80,000 or more and Mw180,000 or less. If the molecular weight of the styrene-butadiene block copolymer is within the above range, it is easy to form a convex portion 18 of the most suitable size. In addition, from this viewpoint, the molecular weight of the styrene-butadiene block copolymer is more preferably Mw100,000 or more and Mw160,000 or less, and further preferably Mw120,000 or more and Mw160,000 or less. The molecular weight can be calculated by GPC.
[0077] like Figure 3 As shown, by the self-organization of the diblock copolymer of appropriate composition, in the surface layer 16, the phase 17a composed of one block polymer component of the diblock copolymer and the phase 17b composed of the other block polymer component are arranged in the thickness direction. Moreover, for example, in the case of a styrene-butadiene block copolymer, the phase 17a composed of the butadiene block polymer component is arranged at the bottom in the thickness direction, and the phase 17b composed of the styrene block polymer component is arranged above it. The convex portion 18 is composed of the phase 17b composed of the styrene block polymer component in the diblock copolymer.
[0078] The surface material can be formed of a coating material containing a diblock copolymer. The surface layer 16 can be formed by applying a coating material as the surface material on the outer peripheral surface of the elastomer layer 14, drying and self-aggregating, thereby forming a surface layer having a plurality of fine protrusions 18 uniformly.
[0079] In order to impart conductivity, conductive agents such as carbon black, graphite, conductive titanium oxide, conductive zinc oxide, conductive tin oxide, ion conductive agents (quaternary ammonium salts, borates, surfactants, etc.) may be appropriately added to the surface layer 16. In addition, various additives may be appropriately added as needed. In addition, roughness forming particles may be added to the surface layer 16 to ensure surface roughness, or roughness forming particles may not be added.
[0080] The surface layer 16 preferably contains carbon black. If the surface layer 16 contains carbon black, excellent conductivity can be exerted. In the surface layer 16, the content of carbon black is preferably 5 parts by mass or more and 50 parts by mass or less relative to 100 parts by mass of the styrene-butadiene block copolymer. More preferably, it is 10 parts by mass or more and 40 parts by mass or less.
[0081] The roughness forming particles form surface irregularities in the surface layer 16. Examples of the roughness forming particles include resin particles, silica particles, and the like. Examples of the resin particles include polyurethane particles, silicone particles, and acrylic particles. The average particle size of the roughness forming particles is preferably within a range of 3 to 50 μm. The average particle size of the roughness forming particles can be calculated by the median particle size using a laser diffraction particle size distribution measuring device.
[0082] The thickness of the surface layer 16 is not particularly limited, but is preferably in the range of 0.01 to 100 μm, more preferably in the range of 0.1 to 20 μm, and even more preferably in the range of 0.3 to 10 μm. 7 ~10 12 Ω·cm, more preferably 10 8 ~10 11 Ω·cm, more preferably 10 9 ~10 10 In the range of Ω·cm.
[0083] The conductive roller 10 can be manufactured, for example, as follows. First, the shaft 12 is coaxially disposed in the hollow portion of a roller forming mold, a rubber composition is injected, and after heating and curing, the rubber composition is formed on the surface of the shaft 12 by demolding or extruding the rubber composition on the surface of the shaft 12, thereby forming an elastic layer 14 on the outer periphery of the shaft 12. Next, a surface layer forming composition is applied to the outer periphery of the formed elastic layer 14, and heat treatment is performed as needed to form a surface layer 16. In this way, the conductive roller 10 can be manufactured.
[0084] The surface layer forming composition is composed of the above-mentioned main material, conductive agent, and other additives contained as needed. As other additives, crosslinking agents, leveling agents, surface modifiers, etc. of polymer components can be listed. From the viewpoint of adjusting viscosity, the surface layer forming composition preferably appropriately contains organic solvents such as methyl ethyl ketone (MEK), toluene, acetone, ethyl acetate, butyl acetate, methyl isobutyl ketone (MIBK), THF, DMF, methanol, ethanol, etc. Water-soluble solvents and other solvents. As a coating method, various coating methods such as roller coating, dipping, and spraying can be applied.
[0085] According to the conductive roller 10 of the above structure, a plurality of convex portions 18 are formed on the outer peripheral surface of the surface layer 16. The convex portions 18 are hemispherical, the front ends of the convex portions 18 are formed by curved surfaces, and the height h of the convex portions 18, the width W of the convex portions 18, and the width W of the convex portions 18 relative to the interval d of the convex portions 18 are within a specific range. In this way, since the surface layer 16 has a plurality of fine and uniform nano-level convex portions 18 on its outer peripheral surface, dirt such as toner, toner external additives, and paper dust slides off, and adhesion of dirt (toner and paper dust) is suppressed.
[0086] Then, if Figure 4 As shown, the conductive belt (endless belt) 20 includes an elastic layer 24 and a surface layer 26 formed on the outer peripheral surface of the elastic layer 24. The elastic layer 24 is a layer (base layer) that becomes the base of the conductive belt 20. The surface layer 26 is formed as a layer exposed on the surface of the conductive belt 20.
[0087] The elastic layer 24 has the same structure as the elastic layer 14 of the conductive roller 10. The surface layer 26 has the same structure as the surface layer 16 of the conductive roller 10. The conductive belt 20 also exhibits the same effects as those of the conductive roller 10.
[0088] As mentioned above, although embodiment of this invention was demonstrated, this invention is not limited to the said embodiment at all, Various changes can be made within the range which does not deviate from the summary of this invention.
[0089] For example, in the above embodiment, the convex portion 18 is shown to be hemispherical, but the convex portion 18 is not limited to a hemispherical shape as long as it has a curved surface at the tip. In addition, the hemispherical shape may be a hemisphere within a sphere or a hemisphere within an ellipsoid.
[0090] In addition, for example, in the above-mentioned embodiment, the surface layer 16 is in contact with the elastomer layer 14 and is composed of one layer, but other layers may be present between the surface layer 16 and the elastomer layer 14. As other layers, a resistance adjustment layer and the like can be listed. In addition, the surface layer 16 may also be composed of two layers. The lower layer of the surface layer composed of two layers is composed of, for example, a layer containing roughness forming particles, and the upper layer is composed of a layer having the above-mentioned fine structure, or may be a layer not containing roughness forming particles. The polymer component of the lower layer may be the same as the polymer component of the upper layer, or may be a different component such as polyamide, acrylic resin, polyurethane resin, silicone resin, fluoropolymer, etc.
[0091] Example
[0092] Hereinafter, the present invention will be described in detail using Examples and Comparative Examples.
[0093] (Example)
[0094] <Preparation of surface layer forming composition>
[0095] 100 parts by mass of a styrene-butadiene block copolymer and 30 parts by mass of carbon black were added to 495 parts by mass of MEK, and dissolved in a steam oven at 50° C. for 3 hours to prepare a surface layer forming composition.
[0096] <Formation of the surface layer>
[0097] The surface layer forming composition was applied to a PET sheet (30 cm × 30 cm) with a thickness of 100 μm by a bar coating method (coating size: 20 cm × 10 cm). Then, air drying was performed at room temperature for about 1 hour to volatilize the solvent, and a film with a thickness of about 20 μm was formed. Thus, a surface layer was formed.
[0098] (Comparative Example 1-2)
[0099] A surface layer was formed in the same manner as in Example.
[0100] The materials used for the surface layer forming composition are as follows.
[0101] Styrene-butadiene block copolymer <1>: "ASAFLEX825" manufactured by Asahi Kasei (styrene content: 78 mass %, styrene block copolymer content: 50 mol %, molecular weight: Mw: 140,000)
[0102] Styrene-butadiene block copolymer <2>: "ASAFLEX840" manufactured by Asahi Kasei (styrene content: 76% by mass, styrene block copolymer content: 56 mol%, molecular weight: Mw: 150,000)
[0103] Styrene-butadiene block copolymer <3>: "ASAFLEX805" manufactured by Asahi Kasei (styrene content: 77% by mass, styrene block copolymer content: 76 mol%, molecular weight: Mw: 10,5000)
[0104] Styrene-butadiene block copolymer <4>: "ASAFLEX830" manufactured by Asahi Kasei (styrene content 70 mass %, styrene block copolymer content 55 mol %, molecular weight Mw 135,000)
[0105] Carbon black: "KETJEN EC300" manufactured by Lion
[0106] The surface microstructure of each surface layer was analyzed. In addition, a toner adhesion test and a paper dust and external additive adhesion test were performed on each surface layer. The measurement method and evaluation method are as follows. The results are shown in the table.
[0107] (Analysis of surface microstructure)
[0108] The height of the convex portion, the width (diameter) of the convex portion, the interval between the convex portions, and the surface roughness Ra are obtained by image analysis using a height image of a scanning probe microscope (SPM). The interval between the convex portions is obtained based on the lengths of the highest points of adjacent convex portions. The surface roughness Ra is the arithmetic mean roughness. After obtaining an SPM height image from any two points of the produced film, each value is calculated for any three points at one point, and each value is expressed as an average. The photograph of the scanning probe microscope (SPM) is shown in Figure 5 . Figure 5 (a) is Example 1, Figure 5 (b) in Example 2, Figure 5 (c) is Comparative Example 1, Figure 5 (d) in the figure is Comparative Example 2.
[0109] (Toner adhesion test)
[0110] The surface of each surface layer was completely coated with toner (about 5 μm in size) and centrifuged at 12,000 rpm. The surface of the surface layer after centrifugation was observed under a microscope, and the area of the part with toner attached was detected using ImageJ, which was used as the toner attachment rate. A toner attachment rate of 25% or less was "0", and a toner attachment rate of 26% or more was "×".
[0111] (Paper dust and external additive adhesion test)
[0112] Assuming paper dust, calcium carbonate below 100nm was used, and assuming that the colorant was an external additive, magnesium oxide below 100nm was used. The surface of each surface layer was completely coated with calcium carbonate and magnesium oxide, and after covering the surface with a PET sheet (thickness 130μm), a roller with a load of 5kg was moved back and forth 10 times on the PET sheet to apply a physical load. For the sample obtained by peeling the PET sheet, air was blown from a distance of 10cm, and the surface of the surface after blowing was observed under a laser microscope. The area of the part with dirt attached was detected using ImegeJ, and it was used as the attachment rate of paper dust and external additives. The attachment rate of paper dust and external additives was "0" if it was less than 18%, and "×" if it was more than 19%.
[0113]
Table 1
[0114]
[0115] In Comparative Example 1, a block copolymer such as Figure 5 As shown in (c) in FIG. 1 , a layered structure is formed on the surface. Therefore, the contact area with relatively small dirt such as paper dust and toner external additives becomes large, and the effect of removing small dirt is poor. In Comparative Example 2, a block copolymer is used as the surface layer material, such as Figure 5 In (d), as shown in Table 1, the size of the convex portion is too small, and the effect of removing relatively large dirt such as toner is poor.
[0116] In contrast, in the embodiments, block copolymers such as Figure 5 (a) Figure 5 As shown in (b) in the figure, a plurality of convex portions are formed on the surface of the surface layer, the convex portions are hemispherical and the front ends are formed by curved surfaces. In addition, the height of the convex portions, the width (diameter) of the convex portions, and the size of the width of the convex portions relative to the intervals between the convex portions are within a specific range. Therefore, the effect of removing relatively large dirt such as colorant and the effect of removing relatively small dirt such as paper dust and colorant external additives are both excellent.
[0117] As mentioned above, although embodiment and Example of this invention were described, this invention is not limited at all to the said embodiment and Example, Various changes can be made within the range which does not deviate from the summary of this invention.
[0118] Description of Reference Numerals
[0119] 10: conductive roller;
[0120] 12: Axis;
[0121] 14: Elastomer layer;
[0122] 16: surface;
[0123] 18: convex part;
[0124] 20: conductive tape;
[0125] 24: Elastomer layer;
[0126] 26: surface;
[0127] h: height of the convexity;
[0128] W: convex width;
[0129] d: interval between convex parts;
[0130] 17a: Phase composed of butadiene block polymer components;
[0131] 17b: Phase composed of styrene block polymer components.
Claims
1. A conductive member for an electrophotographic device, wherein: The electroconductive member for an electrophotographic device comprises an elastic layer and a surface layer formed on an outer peripheral surface of the elastic layer. A plurality of convex portions are formed on the outer peripheral surface of the surface layer, The front end of the convex portion is formed by a curved surface, The height of the protrusion is not less than 1.0 nm and not more than 10 nm, The width of the convex portion is greater than or equal to 1.0 nm and less than or equal to 100 nm, The width of the convex portion is greater than or equal to 0.5 and less than or equal to 1.5 relative to the interval between the convex portions.
2. The conductive member for an electrophotographic apparatus according to claim 1, wherein The convex portion is hemispherical.
3. The conductive member for an electrophotographic apparatus according to claim 1 or claim 2, wherein: The surface roughness Ra of the surface layer is greater than or equal to 0.5 nm and less than or equal to 10 nm.
4. The conductive member for an electrophotographic apparatus according to any one of claims 1 to 3, wherein The distance between the protrusions is greater than or equal to 1.0 nm and less than or equal to 100 nm.
5. The conductive member for an electrophotographic apparatus according to any one of claims 1 to 4, wherein The surface layer is composed of styrene-butadiene block copolymer.
6. The conductive member for an electrophotographic apparatus according to claim 5, wherein The styrene amount of the styrene-butadiene block copolymer is 71% by mass or more and 85% by mass or less, and the styrene block copolymer amount of the styrene-butadiene block copolymer is 40% by mole or more and 75% by mole or less.
7. The conductive member for an electrophotographic apparatus according to any one of claims 1 to 6, wherein The surface layer contains carbon black.
8. The conductive member for an electrophotographic apparatus according to any one of claims 1 to 7, wherein The surface layer is composed of a self-organized film of a diblock copolymer.
9. The conductive member for an electrophotographic apparatus according to claim 8, wherein The diblock copolymer has a structure in which a phase composed of one block polymer component and a phase composed of the other block polymer component are arranged in parallel in the thickness direction.
10. The conductive member for an electrophotographic apparatus according to claim 9, wherein The diblock copolymer is a styrene-butadiene block copolymer, wherein a phase composed of a styrene block polymer component is disposed on a phase composed of a butadiene block polymer component.
11. The conductive member for an electrophotographic apparatus according to claim 10, wherein The convex portion is constituted by a phase composed of a styrene block polymer component in the diblock copolymer.
Citation Information
Patent Citations
Charging roller and charging device
JP2013076861A
Charging roller
JP2013076862A